2020
DOI: 10.1177/1045389x20959454
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of a planar beating micro-swimmer constructed using functional fluid

Abstract: The dynamics of a flexible micro-swimmer that contains superparamagnetic beads of different diameter in an oscillating field is studied experimentally. Two types of artificial swimmers are fabricated to determine the flexing characteristics. The effect of key parameters that dominate the motion of the swimmer is determined. The flexibility initially increases linearly with the frequency and reaches a maximum value at a specific frequency. The field intensity has no significant effect on the flexibility when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…All swimmers consisted of different numbers of magnetic microparticles of different sizes. Some previous investigations on the effect of the frequency have shown that a microbead chain or swimmer can be manipulated with a stable structure or efficient movement at a frequency of 7–10 Hz [ 35 , 36 ]. Therefore, all the swimmers were subjected to an oscillating frequency of f = 10 Hz in this study.…”
Section: Resultsmentioning
confidence: 99%
“…All swimmers consisted of different numbers of magnetic microparticles of different sizes. Some previous investigations on the effect of the frequency have shown that a microbead chain or swimmer can be manipulated with a stable structure or efficient movement at a frequency of 7–10 Hz [ 35 , 36 ]. Therefore, all the swimmers were subjected to an oscillating frequency of f = 10 Hz in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Less flexible microbead swimmers can also be assembled in the absence of filaments using the particle's magnetic dipole interactions in a static magnetic field. These swimmers of varying bead diameters achieve nonreciprocal motion because of structural deformation within its cyclic motion 21 . However, the assembled structure of these flexible swimmers are found to be unstable and achieve low propulsion efficiencies 22 .…”
Section: Introductionmentioning
confidence: 99%
“…These swimmers of varying bead diameters achieve nonreciprocal motion because of structural deformation within its cyclic motion. 21 However, the assembled structure of these flexible swimmers are found to be unstable and achieve low propulsion efficiencies. 22 It has been shown that for non-flexible swimmers, while the shape of an object is essential, the orientation of its transverse magnetic dipole governs swimming.…”
Section: Introductionmentioning
confidence: 99%